Answer:
m∠CBD = m∠CDB ⇒ proved
Step-by-step explanation:
Let us solve the question
∵ AB ⊥ BD ⇒ given
→ That means m∠ABD = 90°
∴ m∠ABD = 90° ⇒ proved
∵ ED ⊥ BD ⇒ given
→ That means m∠EDB = 90°
∴ m∠EDB = 90° ⇒ proved
∵ ∠ABD and ∠EDB have the same measure 90°
∴ m∠ABD = m∠EDB ⇒ proved
∵ m∠ABD = m∠ABC + m∠CBD
∵ m∠EDB = m∠EDC + m∠CDB
→ Equate the two right sides
∴ m∠ABC + m∠CBD = m∠EDC + m∠CDB
∵ m∠ABC = m∠EDC ⇒ given
→ That means 1 angle on the left side = 1 angle on the right side, then
the other two angles must be equal in measures
∴ m∠CBD = m∠CDB ⇒ proved
Answer: x=3.4
Step-by-step explanation:
0.5x + 4.2 = 5.9 \\ 0.5x = 5.9 - 4.2 \\ 0.5x = 1.7 \\ x = 1.7 \div 0.5 \\
It 20:1
<span>This is a basic math problem which can be solved by simply dividing 300 by 15.</span>
Answer:
6 units squared
Step-by-step explanation:
you take the squares that are split up and find another one that matches with it to make a full square